The Role of International Broadcasting Media in Building Public Diplomacy Bridges - Faisal Aziz, Muhammad; Amalia , Rizki Septin (LPPPIPublishing, 2026)
International broadcasting media play an important role in public diplomacy as a tool to build national image, strengthen international relations, and influence global public opinion. With the ability to disseminate information to foreign audiences, this type of broadcasting has become a key element in diplomatic strategy in the era of globalization and digitalization. Joseph Nye's concept of soft power emphasizes the appeal of culture in shaping perceptions and foreign policy. This study uses a descriptive-analytical qualitative approach to understand the role of international broadcasting in public diplomacy. Countries that invest in global broadcasting services, such as Deutsche Welle, have succeeded in showcasing democratic values and culture, thereby enhancing their reputation and international relations.